CONCOMITANT PSORIASIS VULGARIS AND METABOLIC SYNDROME: A CASE REPORT - Khairunnisa, Qanita (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Among the various dermatological conditions, psoriasis assumes significant relevance concerning Metabolic Syndrome (MetS). A 57-year-old man presents with pruritic and scaly erythematous plaque on the right ankle persisting for four weeks. The dermatological examination uncovered a noticeable erythematous plaque with a scaly surface on the right ankle, conclusively observed as psoriasis clinical features. Physical examination for metabolic syndrome indicated blood pressure readings of 160/100 mmHg and central obesity with a waist circumference of 98 cm. The psoriasis treatment involves the use of topical corticosteroids and emollients, along with oral metabolic medication consisting of simvastatin and amlodipine, and lifestyle modifications to treat the metabolic disorder. Metabolic syndrome leads to an elevation in the synthesis of pro-inflammatory cytokines, which are shared characteristics with psoriasis. Following comprehensive therapy of ten days of topical treatment and lifestyle modifications, the patient experienced an improvement in the active psoriatic lesions, despite the presence of metabolic disorders.